Real estate investor’s checklist : - Irwin, Robert (McGraw-Hill, 2006)
This one-of-a-kind guide delivers real, nuts-and-bolts knowledge on every aspect of finding, purchasing, renovating, managing, and selling property. You'll find proven tactics and step-by-step guidance on investing in single-family homes, apartment buildings, office space, commercial properties, and even undeveloped land.